1998
DOI: 10.1046/j.1365-2222.1998.00400.x
|View full text |Cite
|
Sign up to set email alerts
|

Occupational respiratory hypersensitivity caused by preparations containing acrylates in dental personnel

Abstract: The results indicate that acrylates constitute an important hazard for dental workers. The mechanism of respiratory hypersensitivity is still unknown, and it is probably not IgE-mediated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
67
0
1

Year Published

2002
2002
2012
2012

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(70 citation statements)
references
References 27 publications
2
67
0
1
Order By: Relevance
“…The potential occupational risk factors include chemical, physical, psychological, ergonomic, and other job-related factors Jacobsen, 1990, 1991;Jacobsen and Pettersen, 1993;Jacobsen et al, 1996;Wiltshire et al, 1996]. The health effects of concern include: potential adverse respiratory effects from inhalation of dusts from grinding and polishing of metal alloys, resins, ceramics, plaster, and the abrasives used for polishing [Choudat, 1994;Parks et al, 1999;Kelleher et al, 2000] or acrylates [Savonius et al, 1993;Piirilä et al, 1998;Nayebzadeh et al, 2000]; dermatitis from contact with acrylates and metals [Lee et al, 2001]; neurotoxicity [Seppäläinen and Rajaniemi, 1984] or disturbance of olfaction [Braun et al, 2002] by methyl methacrylate (MMA) monomer; genotoxic damage in lymphocytes possibly related to occupational exposure to chromium, cobalt, and nickel [Burgaz et al, 2002], and health complaints caused by noises, vibration of handpieces, and long working hours [Jacobsen and Pettersen, 1993;Jacobsen et al, 1996].…”
Section: Introductionmentioning
confidence: 98%
“…The potential occupational risk factors include chemical, physical, psychological, ergonomic, and other job-related factors Jacobsen, 1990, 1991;Jacobsen and Pettersen, 1993;Jacobsen et al, 1996;Wiltshire et al, 1996]. The health effects of concern include: potential adverse respiratory effects from inhalation of dusts from grinding and polishing of metal alloys, resins, ceramics, plaster, and the abrasives used for polishing [Choudat, 1994;Parks et al, 1999;Kelleher et al, 2000] or acrylates [Savonius et al, 1993;Piirilä et al, 1998;Nayebzadeh et al, 2000]; dermatitis from contact with acrylates and metals [Lee et al, 2001]; neurotoxicity [Seppäläinen and Rajaniemi, 1984] or disturbance of olfaction [Braun et al, 2002] by methyl methacrylate (MMA) monomer; genotoxic damage in lymphocytes possibly related to occupational exposure to chromium, cobalt, and nickel [Burgaz et al, 2002], and health complaints caused by noises, vibration of handpieces, and long working hours [Jacobsen and Pettersen, 1993;Jacobsen et al, 1996].…”
Section: Introductionmentioning
confidence: 98%
“…John et al found that manicurists and nail sculptors were at increased risk of spontaneous abortion [10]. Health effects have been well documented in other workers, such as dental technicians, who work with one of the principal chemicals used in nail salons: ethyl methacrylate [11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…In our 3 case reports, the observation of delayed bronchial responses with positive patch tests to LMW agents such as DGEBA or HEMA suggest that expiratory troubles could be linked to a cell-mediated mechanism 16) . The absence of specific IgE to acrylates, methacrylates or human conjugated acrylate-albumin in the individuals with ACD and OA 31) , the absence of positive prick tests to the same conjugated substances 31,32) , and the inconstant presence of specific IgE in asthma to epoxy components 16,17) do not suggest an IgE mechanism. Nevertheless, the absence of specific IgE or positive prick tests to a specific agent often occurs in immediate type hypersensitivity and does not indicate a mechanism of delayed type hypersensitivity.…”
Section: Discussionmentioning
confidence: 99%